Superabsorbent polymer balls as foreign bodies in the nasal cavities of children: our clinical experience - Sai-hong Han; Yong-chao Chen; Zhi-xiong Xian; Yi-shu Teng (BMC, 2021)
Abstract Objective To summarize the clinical diagnosis and treatment of superabsorbent polymer balls as nasal foreign bodies in children. Methods We retrospectively analysed the clinical data concerning 12 cases of superabsorbent polymer balls as nasal foreign bodies in children and summarized the corresponding clinical features, methods of diagnoses and treatment, and prognoses. Results Twelve children with superabsorbent polymer balls as foreign bodies in their nasal cavities presented with relatively severe symptoms, such as congestion, runny nose, and nasal swelling. When such foreign bodies stay in the nasal cavity for a prolonged period, patients may suffer from general discomfort, such as agitation, poor appetite and high fever. Most of the children had to undergo nasal endoscopy under general anaesthesia to have the foreign bodies completely removed. An intraoperative examination revealed significant mucosal injury within the nasal cavity. With regular follow-up visits and adequate interventions, all the patients recovered. Conclusion The longer superabsorbent polymer balls remain in the nasal cavity, the more damaged the nasal mucosa will be. It is challenging to remove such foreign bodies in the outpatient setting. Transnasal endoscopy under general anaesthesia appears to be safer and more effective in such cases. Since the nasal mucosa is injured to varying degrees, postoperative follow-up and treatment are equally important for preventing the occurrence of complications.